PENEGAKAN HUKUM TERHADAP PEJABAT NEGARA PELAKU TINDAK PIDANA PENYALAHGUNAAN KEWENANGAN DALAM PENGADAAN BARANG DAN JASA OLEH PEMERINTAH - Fitri Mastuti Nurul Fuadah; Tofik Yanuar Chandra; Hedwig Adianto Mau (Journal of Innovation Research and Knowledge, 2025)
The phenomenon of abuse of power in government procurement of goods and services often occurs due to opportunities arising from weaknesses in the system of oversight and internal control. State officials involved in this process often exploit their positions and authority to gain personal or group benefits. Abuse of power by state officials in the procurement of goods and services is one form of corruption that has serious consequences for national development. The theories employed in this study are the theory of law enforcement and the theory of legal certainty. This research is a normative law research utilizing the statute approach, case approach, and conceptual approach. The types and sources of legal materials used in this research are categorized into three groups: primary legal materials, secondary legal materials, and tertiary legal materials. To obtain relevant materials for the discussion in this paper, the author used library research techniques, analyzed through a normative approach (descriptive-qualitative). The research findings indicate that the authority of state officials in the procurement of government goods and services is regulated in the Penal Code (Articles 209, 415, 417, and 421), as well as other legislative regulations such as Article 3 of Law Number 31 of 1999 jo Law Number 20 of 2001, and Presidential Regulation Number 16 of 2018 jo Presidential Regulation Number 12 of 2021, to prevent abuse of office for personal gain. Law enforcement against state officials who abuse their authority in procurement should be carried out fairly, transparently, and decisively to prevent corruption that harms the state. Deviations such as collusion, bribery, and abuse of office often occur due to weak oversight and a corrupt bureaucratic culture. The imposition of criminal sanctions based on Law Number 31 of 1999 jo Law Number 20 of 2001 as a last resort (ultimum remedium) aims to create a deterrent effect and ensure legal certainty.